Fresno County Young Lawyers Association 8th Annual Channel 18 Law Quiz Program - Watkins, Howard::::::::: (1988)
Judges Gary Austin, Stephen Henry, Jane York, and Justice James Ardaiz with Moderator Colin Daugherty Colin Daugherty also KVPT Station Manager